The Effect of Model Variations on Chemistry Learning Outcomes - Lukman, Isna Rezkia; Unaida, Ratna; Setiawaty, Sri; Sabrina, Najiha; Zahara, Zahara (IJECA (International Journal of Education and Curriculum Application), 2022)
One of the successes in the learning process can be seen from the learning outcomes of students. One of the factors that support this is external factors. External factors are factors that come from outside the learner, such as model variations. The purpose of this study was to determine whether there is an influence of model variations in chemistry learning on chemistry learning outcomes in Lhokseumawe City. This research used a quantitative approach, the type of research was ex post facto, and the research design was regression. The population in this study was all students who were in Grade XI Science Senior High School, while the sampling technique in this study was cluster sampling, the sample taken was several students at Senior high schoolsenior high school. Questionnaire was used for data collection instruments. The questionnaire was created based on a Likert scale with 4 answers already available. Data testing using a non-parametric hypothesis test, namely an SPSS-assisted spearman rank correlation test. Based on the hypothesis test, a significant value model variation is obtained from 0.028 < 0.05. It can be concluded that there was a significant influence between the variations of model in chemistry learning on the results of learning chemistry.